Environmental DNA (eDNA) reveals endangered narrow sawfish across Indonesian Reefs. Issue 1 (December 2021) - Sani, L M I; Husna, A K; Subhan, B; Madduppa, H
Abstract: Environmental DNA or eDNA is a powerful method to uncover marine organisms in the seawaters. Furthermore, many marine species are difficult to determine in the sea waters because of their rare existence based on the visual census. In this study, we implemented environmental DNA to investigate the presence of the endangered species of narrow sawfish Anoxypristis cuspidata in Indonesia. Four liters of seawater samples were collected at six locations near the coral reefs ecosystem of Indonesia and filtered at 0.45 μm filter paper. DNA was extracted from the filter paper then Polymerase Chain Reaction (PCR) amplification was performed using the cytochrome c oxidase subunit I (COI) primer and analyzed by Next Generation Sequencing (NGS). The findings revealed that narrow sawfish exist in Indonesian waters, and it also simultaneously showed that environmental DNA could detect rare species. The environmental DNA approach to identifying narrow sawfish can provide reliable results and be used as a survey tool to protect endangered threatened and protected (ETP) species.